A transgenic cell line with inducible transcription for studying (CGG)n repeat expansion mechanisms - I. V. Grishchenko; A. A. Tulupov; Y. M. Rymareva; E. D. Petrovskiy; A. A. Savelov; A. M. Korostyshevskaya; Y. V. Maksimova; A. R. Shorina; E. M. Shitik; D. V. Yudkin (Вавиловский журнал генетики и селекции)
There are more than 30 inherited human disorders connected with repeat expansion (myotonic dystrophy type I, Huntington’s disease, Fragile X syndrome). Fragile X syndrome is the most common reason for inherited intellectual disability in the human population. The ways of the expansion development remain unclear. An important feature of expanded repeats is the ability to form stable alternative DNA secondary structures. There are hypotheses about the nature of repeat instability. It is proposed that these DNA secondary structures can block various stages of DNA metabolism processes, such as replication, repair and recombination and it is considered as the source of repeat instability. However, none of the hypotheses is fully conf irmed or is the only valid one. Here, an experimental system for studying (CGG)n repeat expansion associated with transcription and TCR-NER is proposed. It is noteworthy that the aberrations of transcription are a poorly studied mechanism of (CGG)n instability. However, the proposed systems take into account the contribution of other processes of DNA metabolism and, therefore, the developed systems are universal and applicable for various studies. Transgenic cell lines carrying a repeat of normal or premutant length under the control of an inducible promoter were established and a method for repeat instability quantif ication was developed. One type of the cell lines contains an exogenous repeat integrated into the genome by the Sleeping Beauty transposon; in another cell line, the vector is maintained as an episome due to the SV40 origin of replication. These experimental systems can serve for f inding the causes of instability and the development of therapeutic agents. In addition, a criterion was developed for the quantif ication of exogenous (CGG)n repeat instability in the transgenic cell lines’ genome.